Safety assessment of the process 'RecyPET Hungária', based on RecyPET Hungária technology, used to recycle post‐consumer PET into food contact materials. (30th November 2018) - ,; Silano, Vittorio; Barat Baviera, José Manuel; Bolognesi, Claudia; Brüschweiler, Beat Johannes; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process RecyPET Hungária (EU register number RECYC0146). The input is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, containing no more than 5% of PET from non‐food applications. The flakes are dried and extruded. The output of the extrusion step is cut into pellets in an underwater chamber and then recrystallised. The crystallised pellets may then be fed into a solid‐state polycondensation (SSP) reactor. The recycled plastic is intended for manufacture of bottles for soft drinks or water. The applicant provided a challenge test, but the flakes contaminated with the surrogates and the pellets obtained after extrusion and crystallisation were extracted with n ‐hexane without showing sufficient recovery. The Panel considered the extraction as unreliable and could therefore not conclude on the efficiency of the decontamination process. Furthermore, the flow charts provided by the applicant did not enable a clear identification of the steps relevant for the decontamination efficiency, and no sufficiently clear overview of the operational parameters of the steps of the process and the challenge test was provided. Without this information, a proper safety evaluation could not be performed. The Panel concluded that the process RecyPET Hungária is not sufficiently characterised and the applicant has not demonstrated in an adequately performed challenge test or by other appropriate evidence that the recycling process RecyPET Hungária is able to reduce contamination of the PET input to a concentration that does not pose a risk to human health.